Inhibitory Action of Pisatin, a Phytoalexi'm of Pisum Sativum, for Spore Germination of Plant Fungi. - Siti Muslimah Widyastuti; Fukuji Nonaka; Nobumichi Sako; Kinji Tanaka (Jurnal Ilmu Pertanian, 1989)
-